2016
DOI: 10.1002/aic.15410
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic mesoporous acidic resin for hydroxyalkylation/alkylation of 2‐methylfuran and ketone to high‐density biofuel

Abstract: Hydroxyalkylation/alkylation of biomass‐derived 2‐methylfuran with cyclic ketones (cyclopentanone and cyclohexanone) has great potential in synthesizing high‐density biofuel. But the conversion and selectivity are still unsatisfactory because the in‐situ formed water decreases the acidity of catalyst and induces side reaction. Herein, hydrophobic mesoporous resins with sulfonic acid group (PS) and fluoride sulfonic acid group (PCS) were synthesized by a simple solvothermal reaction and ion exchange treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…31 Cyclopentanone can undergo condensation with valeraldehyde, 32 furfural 33,34 or itself. [35][36][37][38] It can also react with 2-methyl furan through hydroxyalkylation/alkylation, 9,39,40 generating C 10 -C 15 oxygen-containing compounds, and then the C 10 -C 15 oxygencontaining compounds can be converted into high-density diesel or jet fuel by hydrodeoxygenation. Aldol condensation of cyclopentanone and furfural by sodium hydroxide in solution free system achieved 2,5-bis(2-furylmethylidene)cyclopentanone yield of 96.0%.…”
Section: Introductionmentioning
confidence: 99%
“…31 Cyclopentanone can undergo condensation with valeraldehyde, 32 furfural 33,34 or itself. [35][36][37][38] It can also react with 2-methyl furan through hydroxyalkylation/alkylation, 9,39,40 generating C 10 -C 15 oxygen-containing compounds, and then the C 10 -C 15 oxygencontaining compounds can be converted into high-density diesel or jet fuel by hydrodeoxygenation. Aldol condensation of cyclopentanone and furfural by sodium hydroxide in solution free system achieved 2,5-bis(2-furylmethylidene)cyclopentanone yield of 96.0%.…”
Section: Introductionmentioning
confidence: 99%
“…[181,183] High thermal stability is critical for the prevention of deposits generated by high temperature pyrolysis. [184] Cold jet fuel flows through heat exchangers to transfer heat from the aircraft parts to the hydrocarbon fuel. The heated fuel can then be combusted to provide thrust.…”
Section: Decalin and Dimethyldecalinmentioning
confidence: 99%
“…Studies of the HAA reaction of 2-MF with cyclic ketones, suggested that water produced from the reaction had a negative effect on conversion and selectivity. [184] Water is a common product generated during deoxygenation of biomass derivatives that can reduce the activity of traditional acid catalysts. [236][237][238][239][240][241][242][243] To address this issue, Zou and coworkers synthesized a sulfonic acid functionalized resin (PS) and an ionic sulfonic acid-functionalized resin (PCS) by a solvothermal process (Scheme 25).…”
Section: Hydroxyalkylation/alkylationmentioning
confidence: 99%
See 2 more Smart Citations